"Development" is not essential to reduce infant mortality rate in India: experience from the Ballabgarh project. Issue 4 (1st April 2000) - Anand, K; Kant, Shashi; Kumar, Guresh; Kapoor, S K
Abstract : BACKGROUND: India aims to reduce the infant mortality rate (IMR) to below 60 per 1000 live births by 2000. IMR is higher in northern India as compared with south Indian states like Kerala. Any further reduction in IMR needs identification of new strategies. The Ballabgarh project with an IMR of 36 in 1997 can help identify such strategies. OBJECTIVE: To see the trend in reduction of neonatal mortality rate (NNMR) and IMR at the Ballabgarh project, compare it with Kerala and rural India's trend and look at the causes of neonatal and infant mortality. DESIGN: The Comprehensive Rural Health Services Project, Ballabgarh, run by the All India Institute of Medical Sciences, covered an estimated population of 70 079 in 1997. The health care delivery system is on the national pattern. All the deaths are identified during the house visits by the male workers. The cause of death is ascertained by the health assistant based on the symptomatology at the time of death. RESULTS: The trends in reduction of IMR for Ballabgarh, Kerala and rural India are roughly parallel with the IMR of Ballabgarh lying somewhere in between the two. However, the NNMR of Ballabgarh (10.6 in 1996) was comparable to Kerala's NNMR (10.9 in 1992). The proportion of infant deaths occurring during the neonatal period had fallen from 50% in the early seventies to 30% during 1996–97. In 1992–1994, 33.8% of all neonatal deaths were attributable to low birth weight and 37.3% to infective causes. Acute respiratory infection and diarrhoea continue to be the chief cause of postneonatal mortality. CONCLUSION: It is possible to bring down neonatal mortality before postneonatal mortality. The Kerala model, which focuses on social development, may not apply to northern India for sociocultural reasons.